(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Being a prominent literary figure, Eugene O’Neill won friends as well as critics through his plays. Scholarship and criticism on O’Neill’s works is vast and varied. His works are analyzed from various points of views by renowned scholars not only in America but in the parts of the world, including India. It is worthwhile to have a study of the present criticism on O’Neill. The scope of present study will also become evident from the study of the existing criticism on O’Neill. The existing criticism on O’Neill consists of biographies, critical books, collections of critical essays and articles.